PENGARUH HUMAN CAPITAL STRUCTURAL, CAPITAL RELATIONAL CAPITAL DAN EMPLOYEE ENGAGEMENT TERHADAP PRESTASI KERJA PEGAWAI PADA SEKRETARIAT DPRD KABUPATEN KEPULAUAN SELAYAR - Miswar Wahyudi Nasir Leha; Syamsul Alam; Andi Djlalante (AkMen JURNAL ILMIAH, 2020)
This study aims to analyze whether there is an influence between Human Capital, Structural Capital, Relational capital and Employee Engagement on Employee Performance at the Secretariat of the Regional People's Representative Council, Selayar Archipelago Regency. The method used is quantitative descriptive method, the data used are primary data and secondary data generated from distributing questionnaires, direct observation and literature study. The analytical tool used is statistical analysis, namely multiple linear regression analysis with proof of the hypothesis through the t test to prove the relationship between the independent variable and the dependent variable partially and the f test to prove the relationship between the independent variable and the dependent variable simultaneously. The research was conducted by taking a sample of 88 respondents, which is the total number of employees at the Secretariat of the Regional People's Representative Council of the Selayar Islands Regency. This study proves that there is a positive but insignificant influence between the Human Capital variable on Job Performance, there is a positive and significant influence between the Structural Capital, Relational Capital and Employee Engagement variables on Work Performance at the Secretariat of the Regional People's Representative Council of Selayar Islands Regency. This study also proves that there is a positive and significant influence between the variables of Human Capital, Structural Capital, Relational Capital and Employee Engagement together (simultaneously) on Job Performance at the Secretariat of the Regional People's Representative Council of Selayar Islands Regency. This study also shows that the Structural Capital variable is the most dominant variable affecting work performance at the Regional Representative Council Secretariat of the Selayar Islands Regency.